Genetic Research & COMMUNAL NARRATIVES - Davis, Dena S. (The Hastings Center report, 2004)
The risks and benefits of genetic research extend beyond individual subjects. Genetic research can also affect the communities to which the subjects belong, by rewriting the narratives and reconfiguring the identities that members of the community share and live by. These far-ranging effects raise special concerns for obtaining informed consent, for which there is no simple solution.